ADAPTASI NARATIF KISAH-KISAH HEWAN DALAM QUR’AN KE DALAM BUKU CERITA ANAK DARI SUDUT PANDANG TAFSIR AL-JALALAIN - Izzatul Ummah, Zulfa; bin Salman, Abdul Matin (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to examine the narrative adaptation process of animal stories in the Qur'an into children's storybooks, using Tafsir Al-Jalalain as the primary interpretive reference. The focus of this research is to analyze how the messages contained in Qur'anic verses and classical interpretations can be effectively communicated to children through illustrated storytelling media. This study employs a qualitative approach based on literature review, with Linda Hutcheon’s theory of narrative adaptation as the analytical framework. The findings indicate that the adaptation process involves three main aspects: (1) media and style transposition, which refers to the transformation of theological texts into visual-narrative media appropriate for children; (2) reinterpretation, which simplifies the meanings of the verses and tafsir into accessible stories while maintaining the core messages; and (3) intertextuality, which highlights the connections between Qur'anic texts, classical tafsir, and the adapted narratives in children's books. The transformation of narrative elements such as plot, characters, conflict, and moral messages is carried out with consideration of children's cognitive and emotional development, while preserving the integrity of Islamic values. This research concludes that narrative adaptation of Qur'anic animal stories can serve as an effective literacy-based da'wah strategy for introducing Islamic teachings to young audiences in an engaging, visual, and educational manner. Keywords: Narrative Adaptation; Animal Stories in the Qur’an; Tafsir Al-Jalalain; Children’s Storybooks; Linda Hutcheon